Intraoperative tissue expansion in the surgical correction of craniosynostosis. Issue 1 (March 2015) - Doshier, Laura J; Fowler, Daniel; Mcewan, Thomas; Baker, C Lynette; Muzaffar, Arshad R
Background: Wound healing complications can occur after calvarial vault expansion due to tension on the scalp flaps. Objectives: To compare wound healing outcomes in patients with craniosynostosis undergoing calvarial vault expansion with and without intraoperative tissue expansion of the scalp. Methods: The present analysis was an institutional review board-approved, retrospective cohort study involving 40 consecutive patients at the University of Missouri Hospitals and Clinics (Columbia, Missouri, USA) who underwent calvarial vault expansion for nonsyndromic craniosynostosis between June 1, 2009 and June 30, 2012. Patients were divided into two sequential cohorts: the first 20 underwent calvarial vault expansion without intraoperative tissue expansion; the second 20 underwent calvarial vault expansion with intraoperative tissue expansion. The main outcome measures included presence or absence of wound healing complications (persistent scabbing or slow-healing wounds, hardware exposure, need for operative wound revision or healed but widened scars), with documented postoperative follow-up of at least three months. The primary end point was the presence of a well-healed scar; the secondary end point was the need for an operative revision. Results: Patients in the intraoperative tissue expansion group had a higher percentage of well-healed scars (73.6%) than those in the nonexpansion group (42.1%) (P=0.0487). This difference was primarily due to scar widening in the nonexpansion group. Conclusions: The present study demonstrated that the use of intraoperative tissue expansion in patients with nonsyndromic craniosynostosis who underwent calvarial vault expansion resulted in a greater likelihood of a well-healed incision with a lower rate of poor scarring.